Offloading Interventions for the Management of Charcot Neuroarthropathy in Diabetes - Thomas Berhane MSc (Rehab), PostGradDip(Biomech), PostGradDip(Gait analysis); Kanakamani Jeyaraman FRACP(Endo); Mark Hamilton FRACS(Vasc); Henrik Falhammar MD, FRACP(Endo), PhD (Foot & Ankle Orthopaedics)
Background: The use of a nonremovable patellar tendon bearing (PTB) cast in Charcot neuroarthropathy (CA) has not been well studied. We describe the offloading devices, including PTB cast used in our setting for the treatment of CA. Methods: We performed a retrospective observational study on patients with CA and diabetic foot ulcer (DFU) presenting to the multidisciplinary foot clinic at Royal Darwin Hospital, between January 2003 and June 2015. Various immobilization and offloading methods used in CA treatment and their outcomes were analyzed. Results: Ninety-three cases of CA were included. PTB cast (n = 76) and a variety of custom-made removable devices (n = 17) were used for initial offloading. Patients treated with PTB casts were allowed to fully weightbear on the affected limb, as tolerated. Initial offloading was continued until the joint stabilized and ulcer healed (6.5±1.9 months), and then patients were transitioned to various orthotic devices and then to accommodative footwear. At the end of the whole offloading treatment (median duration 13.1 months; range 10-24), patients treated with PTB initially had better outcomes compared with patients treated with removable devices. Conclusion: Immobilization using PTB casting was an effective offloading method for CA with DFU. With our offloading regimen, Indigenous and non-Indigenous patients had similar outcomes. Level of Evidence: Level III, retrospective cohort study.